PROFESIONALITAS APARATUR BIROKRASI KECAMATAN PALU BARAT KOTA PALU DALAM MENJALANKAN TUGAS DAN FUNGSINYA - Kursaid, Nawab (Katalogis, 2013)
This research aims at getting the deep understanding and answer of the facts toward problems releated to the professionalism of bureaucrat staffs of West Palu Sub-district. This was a qualitative research. The informants of this research were the chief of West Palu Sub-district, Secretary of West Palu Sub-district, the section head of the sub-district, and public user of the service. The informants were determined by using purposive sampling technique. Data were collected through observation, interview, and documentation. The technique of data analysis was done through data reduction, data display, and conclusion or verification. The conclusion was obtained from some of the whole configurative activities. The conclusion was also verified during the research. In order to analyze the data, the researcher adopted the Siagian’s theory with the indicators: creativity, innovation, and responsiviness. The research result showed that the professionalism of bureaucrat staffs of West Palu Sub-district, Palu City, was not optimal yet in administering their jobs and functions, because all indicators analyzed did not have yet good result. In addition, some of the public participation improvement programs were not done, because of the limited budget and of the insufficient infrastructures to support the administration of their jobs and functions. The responses of bureaucrat staffs toward public claims were not done yet well.